Partial differential equations : modeling, analysis, computation - 357382 Mattheij, R. M. M.; Rienstra, S. W.; Thije Boonkkamp, J. H. M. ten (Philadelphia, PA : Society for Industrial and Applied Mathematics, 2005)
41